(untitled) (Pedagogy of Higher and Secondary Education, 2013)
Romanets V. M. Тhe formation of professional ideology of the future lecturer of foreign literature as aim and social significant result of his specialized preparation in high education establishment. The article presents the results of theoretical analysis of the problem of formation of professional worldview of the future teacher of foreign literature in condition of multicultural society. Particular attention is given to coverage conceptual principles of organization of this process by grounding the leading principles of the course «Foreign literature».